Effects of degraded operation modes on reliability and performance of manufacturing cells. (1st January 2012) - Savsar, Mehmet
In this study, operational performance of a manufacturing cell is analysed under three possible scenarios: fully reliable equipment; unreliable equipment subject to corrective maintenance and unreliable equipment allowed to operate under degraded mode also subject to corrective maintenance of different degrees. Stochastic models are utilised to determine various performance measures under various operational scenarios as mentioned. Performance measures included the productivity and reliability of the system as well as the utilisation of its components, under various operational conditions, including equipment failures and fault-tolerant states. The model and the results can be useful for design engineers and operational managers to analyse performance of a system at the design or operational stages.